2017
DOI: 10.4183/aeb.2017.454
|View full text |Cite
|
Sign up to set email alerts
|

Middle Term Impact of Sleeve Gastrectomy on Major Cardiovascular Risk Factors in a Group of Romanian Obese Patients

Abstract: Background and aim. The goals of bariatric surgery are to improve the quality of life by lowering body mass index (BMI) but also to treat obesity comorbidities. The aim of our study was to evaluate the impact of laparoscopic sleeve gastrectomy (LSG) on metabolic parameters. Methods. 85 obese patients treated by bariatric surgery LSG procedure were included in the study. Basal, 6 and 12 months after surgery serum glucose levels and lipid fractions were measured. Metabolic syndrome criteria according to IDF 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…Similar to other studies (12,20,(24)(25)(26), we observed an early improvement of glucose homeostasis, followed by a stabilization of glycemic parameters.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to other studies (12,20,(24)(25)(26), we observed an early improvement of glucose homeostasis, followed by a stabilization of glycemic parameters.…”
Section: Discussionsupporting
confidence: 92%
“…Taken into consideration the chronic history of obesity, longer observation most probably might reveal more beneficial clinical effects. Bariatric surgery has been shown significant beneficial effects on metabolic syndrome features (17,18), and on major cardiovascular risk factors (19). Likewise, patients in our study demonstrated favorable changes in blood glucose, insulin, HbA1c, CRP, leptin, adiponectin levels, heart rate, sABP 4 years after the LAGB.…”
Section: Discussionsupporting
confidence: 71%